Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea: Megachilidae: Anthidiini) with description of a new species from China - Niu, Ze-Qing; Ascher, John S.; Griswold, Terry; Zhu, Chao-Dong (Zootaxa, 2019)
This revision of the bee genus Bathanthidium Mavromoustakis, 1953, treats 12 species, with 11 recorded from China, including Bathanthidium fengkaiense Niu & Zhu, sp. nov.. Two species are proposed as new combinations in genus Bathanthidium: Anthidium (s. str.) bicolor Wu, 2004, A. (s. str.) monganshanensis Wu, 2004. The two new combinations (B. bicolor, B. monganshanense) are in Bathanthidium (Manthidium), previously considered to include only the type species from Burma and Laos (published records from northeastern India and Malaysia are based on misinterpreted localities). Trachusa (Paraanthidium) concavum (Wu, 1962) and Stelis siamensis Friese, 1925 are synonymized with B. binghami (Friese, 1901). Bathanthidium circinatum Wu, 2004 is transferred to Pseudoanthidium Friese forming the new combination P. (s. str.) circinatum (Wu, 2004). The distribution of each species is given, new distribution sites are marked by asterisk (*) especially. Our results confirm that the genus Bathanthidium has higher species diversity than previously documented and that this diversity is centered in China.